2002
DOI: 10.1074/jbc.m206112200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Enzymatic Characterization of a UDP-GalNAc:GlcNAcβ-R β1,4-N-Acetylgalactosaminyltransferase fromCaenorhabditis elegans

Abstract: A common terminal structure in glycans from animal glycoproteins and glycolipids is the lactosamine sequence Gal␤4GlcNAc-R (LacNAc or LN). An alternative sequence that occurs in vertebrate as well as in invertebrate glycoconjugates is GalNAc␤4GlcNAc-R (LacdiNAc or LDN). Whereas genes encoding ␤4GalTs responsible for LN synthesis have been reported, the ␤4GalNAcT(s) responsible for LDN synthesis has not been identified. Here we report the identification of a gene from Caenorhabditis elegans encoding a UDP-GalNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 89 publications
(63 reference statements)
2
61
0
Order By: Relevance
“…The 150-kilobase region between these boundary single nucleotide polymorphisms contains 20 predicted ORFs. Sequencing of cDNA isolated from the bre-4 alleles revealed changes in the enzymatically characterized glycosyltransferase Y73E7A.7 (8). cDNA rescue of a bre-4 mutant confirmed the identity of bre-4.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…The 150-kilobase region between these boundary single nucleotide polymorphisms contains 20 predicted ORFs. Sequencing of cDNA isolated from the bre-4 alleles revealed changes in the enzymatically characterized glycosyltransferase Y73E7A.7 (8). cDNA rescue of a bre-4 mutant confirmed the identity of bre-4.…”
Section: Methodsmentioning
confidence: 88%
“…1B). BRE-4 has been previously characterized biochemically as a UDPGalNAc:GlcNAc ␤1,4-N-acetylgalactosaminyltransferase (Ce␤4 GalNAcT) (8). BRE-4/Ce␤4GalNAcT specifically synthesizes the GalNAc␤1,4GlcNAc sequence commonly found on glycoproteins and glycolipids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its ortholog was also found in mouse. Kawar et al (23) has reported the cloning of a nematode LacdiNAc synthase, Ce␤4GalNAc-T, which is probably an ortholog of human ␤4Gal-T1. ␤4GalNAc-T3 in the present study is a novel glycosyltransferase, and this is the first report of the molecular cloning and characterization of mammal LacdiNAc synthases, ␤4GalNAc-T3 and m␤4GalNAc-T3.…”
Section: Discussionmentioning
confidence: 99%
“…(N,NЈ-diacetyllactosediamine, LacdiNAc), has been cloned and named Ce␤4GalNAcT (23). Ce␤4GalNAcT has Ile at the same position as Tyr-289 of ␤4Gal-T1, and transfers GalNAc to a variety of acceptor substrates with terminal ␤-linked GlcNAc, resulting in the synthesis of the LacdiNAc structure.…”
mentioning
confidence: 99%